Age Difference in Roles of Perceived Social Support and Psychological Capital on Mental Health During COVID-19 - Cao, Shiyue; Zhu, Yue; Li, Pei; Zhang, Wei; Ding, Cody; Yang, Dong (Frontiers in Psychology, 2022)
Due to the outbreak of the Coronavirus Disease-2019 (COVID-19) pandemic and consequent confinement measures, young people are vulnerable to mental health problems. The current study compared a group of 440 young adolescents (10–12 years) and a group of 330 emerging adults (18–25 years) to investigate the extent to which perceived social support and psychological capital (PsyCap) were differentially associated with mental health problems. Participants were asked to report their current psychosocial adaptation status during the COVID-19 pandemic, and data were collected via online questionnaires during a relatively severe period of COVID-19 in China. Results of the multi-group path analysis indicated that the effect of perceived social support on mental health problems was mediated by PsyCap for young adolescents, but not for emerging adults. These results were discussed with respect to the mechanism of how social support and PsyCap serve as protective mental health factors for youth in the context of the COVID-19 pandemic.